Anti-proliferative activities of purified bacteriocin from enterococcus mundtii strain c4l10 isolated from the caecum of Malaysian non-broiler chicken on cancer cell lines - A Yusuf, Moshood; Arief Ichwan, Solachuddin Jauhari; Tengku Abdul Hamid, Tengku Haziyamin (Academic Sciences, 2015)
This study aim at experimenting the effects of the bacteriocin from Ent. mundtii strain C4L10, an apoptogenic properties, that have the ability to inhibit bacteria at the same time the tendency to induce anti-proliferative characteristics on cancer cell lines. A purified bacteriocin from Ent. mundtii C4L10 strain (accession number KC731423) isolated from Malaysian non-broiler chicken was screened for its anti-proliferative activities against four cancer cell lines; breast cancer (MCF7), lung cancer (H1299), colon cancer (HCT116) and oral cancer (HSC3) by an in vitro MTT [3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide], colorimetric assay. The half maximal inhibition, IC 50 values was determined by non-linear regression analysis using the Prism software (Graphpad). Results: The susceptibility of cancer cell lines to the bacteriocin extract was in the order: oral cancer HSC3, breast cancer MCF7, lung cancer, H1299 and colon cancer HCT116 with the IC50 values, 9.00 μg/ml, 11.51 μg/ml, 15.25 μg/ml, and 20.57 μg/ml, respectively. The approximate molecular weight for this purified bacteriocin was 10 kDa, as observed by SDS-PAGE. Bacteriocin from Ent mundtii strain C4L10 could be employed as potential antimicrobial agent and for anti-proliferative agent in cancer control.